ÜLKEMİZDE ASEMPTOMATİK "SAĞLIKLI" HBsAg TAŞIYICILIĞI - ÖZDEMİR, Sebati; KURAL SEZER, Emire; SONSUZ, Abdullah; BAŞARANOĞLU, Metin; ŞENTÜRK, Hakan; Özbay, Gülşen; AKIN, Perihan (Cerrahpaşa Medical Journal, 2019)
Background and Design. This study examines the serologic, biochemical and histopathological features of 233 cases of asymptomatic HbsAg carriers. Asymptomatic HBsAg carrier state is defined as persistent HBsAg positivity for six months and normal serum transaminase values at least in two examinations. Results. Of the orderly observed (average: 4.2 years) 192 cases, 17 had elevated ALT levels below two times normal and in one of them the increase has persisted. The majority of the cases (94%) HBeAg () and antiHBe (+) HBVDNA was positive in 13 cases. AntiHDV has been determined in only two of the 168 cases investigated. AntiHCV was negative in all of the 118 cases investigated. In two cases HBsAg became negative without occurrence of antiHBs. Liver biopsy has been performed in 37 cases and in two of them moderate chronic hepatitis has been detected. In the follow up period none of the cases developed liver cirrhosis or hepatocellular carcinoma. Conclusion. As a result we have concluded that in this country asymptomatic HBsAg carrier state has a benign course and there is no need for routine liver biopsy. But we believe that cases with HBVDNA positivity should be followed up more closely.